PENGARUH KOMUNIKASI ORGANISASI TERHADAP EFEKTIVITAS KERJA PEGAWAI PDAM TIRTA MEDAL SUMEDANG - Arip Rahman Sudrajat; Muhamad Dony Ardiansyah; Yayat (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2019)
This study aims to determine the effect of communication on employee work effectiveness at PDAM Tirta Medal, Sumedang Regency and to determine the relationship between communication and employee work effectiveness at PDAM Tirta Medal, Sumedang Regency. In this study, researchers used survey research methods, while data collection techniques were carried out through library research and field studies consisting of observation, and distributing questionnaires. The collected data is then processed and analyzed through validity test, reliability test, percentage test, normality test, correlation coefficient test, significance test, and coefficient of determination test. The population in this study were 40 employees of PDAM Tirta Medal, Sumedang Regency. For sampling, the technique of disproportionate stratified random sampling was used. The number of samples in this study were 35 people. Communication at PDAM Tirta Medal, Sumedang Regency reached 72.86%. This is included in the good category, so H0 which reads